Implementation of Islamic Religious Education Learning in Growing and Developing Religious Humanism Students - Sutarman Sutarman; Lina Sukanti; Ani Rohaeni; Neneng Sulastri (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The purpose of this study is to find out (1). Describe the PAI learning model in developing religious humanism at SMAN Purwakarta. (2). Describe the religious humanist character of students at SMAN 2 Purwakarta. Methods: This study uses a qualitative approach that describes the phenomena that occur in the field. Data collection techniques through (1). In-depth interviews with volunteers to obtain data (2). Direct observation of the field to find phenomena that occur in the field (3). Study documentation to complete data in the form of photos, important notes, archives, and others related to the research focus. The conclusions are: (1). PAI learning models in developing religious humanism include exemplary models, question and answer models, discussion models, project models and practice models. (2). The religious humanist character of the students is (1). Respect and obey the teacher, (2). Respect for other school members (3). Loving friends at school and friends outside school (4). Have a passion for learning and high motivation to learn, as well as diligent in learning